Consequences of the surge of new hotels on labour productivity growth in the Spanish hospitality sector - Bienvenido Ortega (European Regional Science Association (ERSA), 2011)
The first aim of this paper is to analyse the main tendencies in employment and regional labour productivity in the Spanish hospitality sector in the period 1987-2004. A second purpose is to analyse the main determinants of sectoral labour productivity. The estimation of an augmented production function is used to this end. This function includes, in addition to the main determinants of labour productivity, some variables linked with the evolution of technical progress in the sector, such as: the mean degree of tourism intensity, average size of establishments, number of hotels and its distribution by category. Besides this, in the empirical model are included a set of variables related to productive capacity utilisation, such as: average length of stay, number of overnight stays per regional bed capacity, and an indicator of regional demand seasonality. This study might allow assessing to what extent the surge of new hotels from 1995 contributed to explain the tendencies in aggregate productivity growth. Moreover, this paper would be useful to determine the main determinants of labour productivity as well as to design policy measures to increase productivity in the sector.
Keywords: 330